(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Public trust in public authorities has always been an important factor and the main indicators of the legitimacy of power. In the modern world, people’s trust is constructed under the influence of various factors. The role of the authority itself is formed under the influence of personal experience, rumors, and above all the media. The media plays an important role here. In the current information society, the media often become the main source of information for the majority of the population. Thus, the images of the executive bodies formed in the media space (media image) can positively or negatively affect the level of citizens’ trust to the authority. This article examines the media image of the Ministry of Education and Science of the Russian Federation. The Ministry of Education plays an important role in the life of any citizen, regardless of status or age. For this reason, the activities of the Ministry of Education are always at the center of attention of all types of media. To analyze the media image of this authority, the author applies frame analysis. Key words: Media image, mediaframe, media, trust, government agency, Ministry of Education and Science.